Komodifikasi Spiritual dan Ketahanan Budaya Hindu: Studi Makanan Satwika dan Praktik Usadha dalam Pariwisata Bali - Sutana, I Gede (Jurnal Penelitian Agama Hindu, 2025)
Bali faces an existential dilemma in maintaining its Hindu cultural identity amid transformation into a global tourism destination, where spiritual commodification threatens the sacred values of traditional practices such as Satwika food and Usadha. This research analyzes the representation of Hindu cultural identity through these two practices and their interaction with cultural tourism dynamics. A qualitative-ethnographic method was applied with case studies in Ubud and Penglipuran villages, involving participant observation, in-depth interviews with 15 informants, and analysis of lontar manuscripts. The results show that 72% of restaurants and Usadha clinics in tourist areas ignore sacred rituals and dana punia principles, replacing them with profit-oriented business models. This commodification transforms spiritual essence into exotic consumption products, risking the disruption of authentic value transmission to younger generations. However, the Penglipuran community has developed cultural resilience strategies through ritual integration in participatory homestays and hybrid Usadha models that combine dana punia with commercial rates. The research affirms that the preservation of Balinese Hindu cultural identity depends on creative adaptation that maintains harmony between spirituality, ecology, and economy. Theoretically, this research contributes to cultural tourism theory by presenting the concept of adaptive cultural resilience and enriching Hindu cultural resilience studies by proving that ritual flexibility based on Tri Hita Karana is more effective than traditional rigidity. These findings enrich glocalization discourse by demonstrating the capacity of local wisdom to create cultural sustainability amid globalization pressures.